Comparison of drilling and helical milling process for holes in titanium alloy - D. S. Makashin; D. A. Blokhin (Омский научный вестник)
Drilling holes in titanium alloy VT-3 is a difficult task due to its poor machinability. The evaluation of the helical milling process is carried out by comparing the axial force, surface roughness and diametrical accuracy of the hole with the conventional drilling process. Holes created with helical milling have a high surface quality at lower axial feed, while the drilling process is accompanied by a higher axial feed, which leads to vibration of the cutting tool. When manufacturing high-precision holes in the elements of fuel control equipment, it is recommended to use helical milling.